2016
DOI: 10.1155/2016/7141523
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antibacterial Potential of Silver Nanoparticles: Biogenic Synthesis Utilizing Apple Extract

Abstract: The advancement of the biological production of nanoparticles using herbal extracts performs a significant role in nanotechnology discipline as it is green and does not engage harsh chemicals. The objective of the present investigation was to extract flavonoids in the mode of apple extract and synthesize its silver nanoparticles and ultimately nanoparticles loading into hydrogels. The presence of flavonoids in apple extract was characterized by preliminary testing like dil. ammonia test and confirmatory test b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 24 publications
2
24
0
1
Order By: Relevance
“…Another report described the antioxidant effect of silver nanoparticles against DPPH, showing 75.16 ± 0.04% inhibition [ 47 ]. The antioxidant activity of silver particles in our study might be because of the capping agents (maleic acid and citric acid) adsorbed at the nanoparticles’ surface, which have been reported to possess antioxidant activities due to their ability to chelate metals, and are, therefore, classified as “preventive” or ‘’synergistic” [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another report described the antioxidant effect of silver nanoparticles against DPPH, showing 75.16 ± 0.04% inhibition [ 47 ]. The antioxidant activity of silver particles in our study might be because of the capping agents (maleic acid and citric acid) adsorbed at the nanoparticles’ surface, which have been reported to possess antioxidant activities due to their ability to chelate metals, and are, therefore, classified as “preventive” or ‘’synergistic” [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ability of a drug to attenuate injuries or to preserve the normal physiological function of the liver after induction of toxicity is the index of its hepatoprotective effect 60. Plant extracts used to synthesize AgNPs can lead to synergistic effects, including an antioxidant effect 61. Results obtained, considering the biochemical and histological parameters, signify that AgNPs were effective in protection against CCl 4 -intoxication.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, silver phyto-nanoparticles obtained from extracts of ornamental flower plants Hyacinthus orientalis and Dianthus caryophyllus (oriental hyacinth and garden clove) were found to have high antioxidant activity [ 207 ]. Salari et al demonstrated that AgNPs synthesized using an aqueous Prosopis farcta fruit extract were excellent free radical “cleaners” [ 208 ]; a similar effect was shown in vitro for an aqueous extract of black Currant pomace [ 209 ], apple extract [ 210 ], leaf extracts of Elephantopus scaber [ 211 ], Indigofera hirsuta [ 212 ], and Tinospora cordifolia [ 213 ]. The most popular used and rapid methods for estimating antioxidant activity are the ABTS (2,2-Azino-bis (3-ethylbenzthiazoline-6-sulfonic acid radical) and DPPH (1,1-diphenyl–2–picrylhydrazyl radical) assays [ 214 ].…”
Section: Biomedical Application Of Agnpsmentioning
confidence: 98%